Sentential particles and clausal typing in the veneto dialects - Munaro, Nicola; Poletto, Cecilia (ZAS Papers in Linguistics, 2004)
In this work we examine several sentential particles, occurring in imperatives, main exclamative and interrogative sentences, which display a uniform syntactic behaviour. We analyse them as heads of high CP projections which require their specifier to be filled either by the wh-item (in sentences where there is one) or by the whole clause, yielding the sentence final position of the particle. The hypothesis that they are C°-heads accounts for their sensitivity to sentence type and for their occurrence only in matrix contexts. We also provide a first sketch of their semantic contribution, showing that they select ‘non standard’ contexts and interact with tense and modality of the verb when the whole CP has moved to their specifier.